Pathogenicity of Beauveria bassiana for adults of Tribolium castaneum ( Col.: Tenebrionidae ) in stored grains - Padín, Susana Beatriz (1997)
Conidia ofBeauveria bassiana were evaluated for activity against adults ofTribolium castaneum, under laboratory conditions closely resembling the stored-grain conditions. Three doses of the fungus were applied in the treatments: 0.1 g, 0.5 g and 1 g per 20 insects/dose/flask. Treated insects and untreated were incubated in broken wheat. There were 5 replications for each test. A total of 1600 treated and control insects used were kept in a climatic chamber (70±5% and 27±2°C) for 45 days. Observations were performed daily and the recording of infected cadavers began when the percentage of mortality exceeded 50%. The evaluation of the efficiency of each dose ofB. bassiana was made 14, 21, 28 and 45 days after inoculation. Mortality of adults that were exposed to the beetles treated with 0.5 g and 1 g of conidia ofB. bassiana / 20 adults was 87 and 85% respectively, within 21 days of exposure. Onset of mortality was further delayed at lower dosage of the fungus; 55% after 21 days. After 28 days there were no difference in mortality between the 0.5 g and 1 g dosages ofB. bassiana. The most efficient treatment was 0.5 g/20 insects, which resulted in a control higher than 50% 14 days post treatment.